Influence of mechanical activation of steel powder on its properties - Vaulina O. Yu. Olga Yurievna; Darenskaya E. A. Elena Anatolievna; Myachin Yu. V. Yury Vladimirovich; Vasiljeva (Vasilyeva) I. E. Inessa Edvinovna; Kulkov S. N. Sergey Nikolaevich (2017, 2017)
Title screen